OPTIMALIZATION AND SOCIALIZATION OF INTERNET-BASED AQUACULTURE MEDIA CONDITION MONITORING TECHNOLOGY, ARSENIK 2 - Prisma Megantoro; Rezi Delfianti; Rizki Putra Prastio; Nayu Nurrohma Hidayah; Marwan Fadhilah; Ahmad Rahmad Muzadi; Muhammad Hudzaifah Abdillah; Heru Dwi Cahyono; Hafizh Alauddin Atallah; Muhammad Rafi Nabil Arsalan (Universitas Airlangga, 2023)
Indonesia's geographical condition, as a maritime country, has a wealth of natural resources in the form of water, which has the potential to support the economy in the aquaculture sector. One of them is the cultivation of freshwater fish ponds as has been carried out by the Maju Rukun Community Group (PokMas) in Ngerong Village, Pasuruan. Lack of equipment and knowledge in monitoring pond water conditions, resulting in problems with the fish nursery process. This is because water is a living medium for aquatic organisms, thus determining the survival of cultivated fish. Therefore, community service activities were held in the form of implementing an appropriate technology device